Students are Almost as Effective as Professors in University Teaching - Jan Feld; Nicolas Salamanca; Ulf Zölitz (Institute of Labor Economics (IZA), 2019)
In a previous paper, we have shown that academic rank is largely unrelated to tutorial teaching effectiveness. In this paper, we further explore the effectiveness of the lowest-ranked instructors: students. We confirm that students are almost as effective as senior instructors, and we produce results informative on the effects of expanding the use of student instructors. We conclude that hiring moderately more student instructors would not harm students, but exclusively using them will likely negatively affect student outcomes. Given how inexpensive student instructors are, however, such a policy might still be worth it.
Keywords: I21; I24; J24; 330; student instructors; university; teacher performance